Math, asked by mounibeauty9778, 6 months ago

Simplification and answer in exponential form of [(2²)³ × 3⁶] × 5⁶ is

Answers

Answered by TheIronGirl
1

Answer:

MARK AS BRAINLIEST

Step-by-step explanation:

For example:

1. 5³ ×5⁶

= (5 × 5 × 5) × (5 × 5 × 5 × 5 × 5 × 5)

= 53+6, [here the exponents are added]

= 5⁹

2. (-7)10 × (-7)¹²

= [(-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7)] × [( -7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7)].

= (-7)10+12, [Exponents are added]

= (-7)²²

3. (12)4 × (12)3

=[(12) × (12) × (12) × (12)] × [(12) × (12) × (12)]

=(12)4+3

=(12)⁷

4. 3² × 3⁵

= 32+5

= 3⁷

5. (-2)⁷ × (-2)³

= (-2)7+3

= (-2)10

6. (49)³ × (49)²

= (49)3+2

= (49)⁵

We observe that the two numbers with the same base are

multiplied; the product is obtained by adding the exponent.

2. Dividing Powers with the same Base

For example:

3⁵ ÷ 3¹, 2² ÷ 2¹, 5(²) ÷ 5³

In division if the bases are same then we need to subtract the exponents.

Consider the following:

2⁷ ÷ 2⁴ = 2724

= 2×2×2×2×2×2×22×2×2×2

= 27−4

= 2³

5⁶ ÷ 5² = 5652

= = 5×5×5×5×5×55×5

= 56−2

= 5⁴

10⁵ ÷ 10³ = 105103

= 10×10×10×10×1010×10×10

= 105−3

= 10²

7⁴ ÷ 7⁵ = 7475

= 7×7×7×77×7×7×7×7

= 74−5

= 7−1

Let a be a non zero number, then

a⁵ ÷ a³ = a5a3

= a×a×a×a×aa×a×a

= a5−3

= a²

again, a³ ÷ a⁵ = a3a5

= a×a×aa×a×a×a×a

= a−(5−3)

= a−2

Thus, in general, for any non-zero integer a,

aᵐ ÷ aⁿ = aman = am−n

Note 1:

Where m and n are whole numbers and m > n;

aᵐ ÷ aⁿ = aman = a−(n−m)

Similar questions